A critique of irrational elements in Africa beliefs - Adekannbi, G.O. (Ibadan Journal of Religious Studies 1(41), 2009)
Various researches show that irrational elements in human beliefs, otherwise known as superstition, just as they were criticized in ancient Greek and Roman societies, have been challenged in Europe and America as well. This paper highlights how individuals and organizations in Arica have similarly raised their voices against the increasing controversial stories of claims of supernatural influences or interferences in human affairs, suppression of thoughts, sexual abuse and extra-judicial inflicting of punishment or killing buy individuals professing authority from spiritual realm. After a brief consideration of the socio-religious atmosphere that engenders the romance with the supernatural sphere, this work shows how the prevalent recourse to mystery in providing reasons for extraordinary occurrences could be most subjective. It then relates how what may seem a private expression of socio-cultural or religious vies is confronted with criticism when it infests the public domain with disquieting concerns. The paper illustrates how practices rooted in superstition are perceived as growing threats to people’s welfare in the continent. When the subject in understood in these terms, more meaning could be added to the search for a solution to sporadic religious, political and social conflicts to Africa.
Keywords: Criticism African reasons meaning practices